To Study Chronic Toxicity for Polyherbal Formulation - Kaspate, Dipti; Narkhede, S.; Dube, A.; Salian, R.; Bartakke, U.; Rao, A.; Sainkar, P.; Takudage, P.; Takras, V.; Pokalwar, N. (Asian Journal of Pharmaceutical Research and Development, 2014)
The objective of the present study to investigate the safety of polyherbal formulation containing Tribulus terrestris, Withania somnifera and Chlorophytum borivilianum by determining its potential toxicity after chronic administration in rats as per OECD guideline No.421. Wistar rats (150-200g) in treatment group I, II and III received polyherbal formulation of 400 mg/kg/day, 800 mg/kg/day and 1600 mg/kg/day (p.o.) respectively for 90 days. After 90 days rats were decapitated and vital organs (brain, heart, kidney, liver, ovary, testis and epididymis) removed, weighed and made histological sections. Result showed no significant treatment-related changes in organ weights and absence of any disease state or lesions in histological sections of brain, heart, liver, kidney observed. But there were changes in weights and histoarchitectural changes (toxic effects) of ovary, testis and epididymis in group wise observed.